Building local research and development capacity for the prevention and cure of neglected diseases: the case of India - Kettler Hannah E.; Modi Rajiv (The World Health Organization, 2001)
This paper examines the proposal to build research and development (R & D) capabilities for dealing with neglected infectious and tropical diseases in countries where they are endemic, as a potentially cost- and time- effective way to fill the gap between the supply of and need for new medicines. With reference to the situation in India, we consider the competencies and incentives needed by companies so that their strategy can be shifted from reverse engineering of existing products to investment in R & D for new products. This requires complex reforms, of which the intellectual property rights agreement is only one. We also consider whether Indian companies capable of conducting research and development are likely to target neglected diseases. Patterns of patenting and of R & D, together with evidence from interviews we have conducted, suggest that Indian companies, like multinational corporations, are likely to target global diseases because of the prospect of much greater returns. Further studies are required on how Indian companies would respond to push and pull incentives originally designed to persuade multinational corporations to do more R & D on neglected diseases.